Pengaruh Konten TikTok dan Influencer Marketing terhadap Keputusan Pembelian dengan Pendapatan sebagai Variabel Kontrol - Didi Andri; Ahmad Fadli; Eko Pratandi; Muhammad Tareq Hanafi Majid (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2026)
This research is conducted to examine how influencer marketing and TikTok content impact the purchasing decisions of Generation Z in the Mataram City area, with income level as a controlled variable. The method applied is a quantitative approach of the causal associative type. The determination of the sample was conducted using purposive sampling techniques, involving 85 individuals from Generation Z in the city of Mataram who are active users of the TikTok application and have been exposed to promotions from influencer figures. Field data collection was conducted using a Likert scale questionnaire, which was then processed using multiple linear regression analysis with the aid of SPSS version 25 software. The research findings indicate the absence of a significant influence of the TikTok content variable on purchasing decisions, as shown by the significance value of 0.740 > 0.05. On the other hand, influencer marketing has a positive and significant impact on consumer decisions, as evidenced by a significance value of 0.001 < 0.05. Meanwhile, income, positioned as a control variable, proved to be the most dominant factor and had a significant influence on the decision to purchase, with a significance level of 0.000 < 0.05. Simultaneous testing shows that the combination of income, influencer marketing, and TikTok content has a significant impact on the decision-making process with a significance value of 0.000 < 0.05. Furthermore, the acquisition of an Adjusted R Square value of 0.903 means that 90.3% of the variation in purchasing decisions can be explained by the research model used.